Diagnostic Accuracy of Xpert Mycobacterium Tuberculosis/Rifampicin in Detecting Pulmonary Tuberculosis from Bronchoalveolar Lavage Fluid in Sputum-Negative Patients: Xpert Mycobacterium Tuberculosis/Rifampicin: Pulmonary TB from Bronchoalveolar Lavage Fluid - Safi, Abdullah; Iqbal, Zafar; Hussain, Zakir; Ullah, Fawad; Shah, Muhammad Khalid; Khan, Muhammad Azeem (Pakistan Journal of Health Sciences, 2026)
Pulmonary Tuberculosis (TB) is also a substantial health issue in high-burden countries like Pakistan. Diagnostic methods such as sputum smear microscopy and culture have limitations in smear-negative cases, necessitating the use of alternative methods. The Xpert MTB/RIF assay is a fast molecular diagnostic option, but its accuracy on bronchoalveolar lavage fluid (BALF) in sputum-negative patients is not well established. Objectives: To determine the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the Xpert MTB/RIF assay on BALF, using culture as the gold standard. Methods: This prospective diagnostic validation study was conducted at Lady Reading Hospital, Peshawar, from May 2025 to September 2025, including 679 adult patients with smear-negative pulmonary TB suspicion undergoing bronchoscopy. BALF samples were tested using smear microscopy, culture (gold standard), and the Xpert MTB/RIF assay. Data were analyzed using SPSS version 25.0. Results: Most of the patients were male 389 (57.3%). The mean age was 41.3 ± 14.2 years. Among 171 culture-positive cases, 145 were also positive by Xpert. Among 508 culture-negative cases, 490 tested negatives with Xpert. Xpert test showed 84.8% sensitivity, 96.5% specificity, 88.9% PPV, 94.9% NPV, and 93.3% diagnostic accuracy. Stratified analysis showed comparable diagnostic metrics across gender and age groups. The AUC of the ROC curve is 0.91, which indicates that Xpert performed excellently in diagnosing TB. Conclusions: Xpert MTB/RIF on BALF provides high diagnostic accuracy for detecting pulmonary TB in sputum-negative patients, with excellent sensitivity, specificity, and predictive values.